2014
DOI: 10.1001/jamaoto.2014.1169
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Emotional Intelligence Training for Otolaryngology Residents and Faculty

Abstract: Emotional intelligence training positively influences patient satisfaction and may enhance medical education and health care outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 19 publications
0
95
0
Order By: Relevance
“…Jensen et al 19 and Dugan et al 20 both reported BarOn EQ-i scores of surgical residents that were highest in stress management and lowest in interpersonal skills. However, these low scores were still above national average.…”
Section: Ei and Personal Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Jensen et al 19 and Dugan et al 20 both reported BarOn EQ-i scores of surgical residents that were highest in stress management and lowest in interpersonal skills. However, these low scores were still above national average.…”
Section: Ei and Personal Characteristicsmentioning
confidence: 99%
“…The current literature essentially serves as a needs assessment that identifies opportunities for improvement or optimization in surgical resident education. Dugan et al 20 presented the only intervention to address the EI of surgical residents along with a longitudinal assessment of EI. After 7 years of an interactive EI training module for both residents and faculty, the authors report a shift in the EI scores of the entire department from the "average" range to the "high average" range.…”
Section: Themes In Surgical Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Some organizations are beginning to evaluate the advantages of using information gained from 360-Degree physician feedback to improve physician emotional intelligence as a way to foster two of the six core competencies (interpersonal and communication skills, professionalism) endorsed by the Accreditation Council for Graduate Medical Education, the American Board of Medical Specialties, and the Joint Commission [16]. Some more progressive organizations have introduced emotional intelligence training for specialty groups as a way to improve patient satisfaction and clinical outcomes [17]. At Brigham and Woman's Hospital in Boston, they have developed a Division of Medical Communications Department to enhance communication efficiency [18].…”
Section: Health Care Applicationsmentioning
confidence: 99%